Poor Sleep Quality Associated With Enlarged Perivascular Spaces in Patients With Lacunar Stroke - Yang, Shuna; Yin, Jiangmei; Qin, Wei; Yang, Lei; Hu, Wenli (Frontiers in Neurology, 2022)
Background and Objective: Enlarged perivascular spaces (EPVS) are considered as an marker of cerebral small vessel diseases and were reported to be associated with brain waste clearance dysfunction. Previous study found that interstitial fluid clearance in the mouse brain occurred mainly during sleep. However, the relationship between sleep quality and EPVS in human haven’t been well understood. Thus, we aimed to investigate the relationship between sleep and EPVS in human. Methods: This retrospective study was conducted in lacunar stroke patients. Patients with EPVS > 10 on one side of the basal ganglia and white matter slice containing the maximum amount were defined as BG-EPVS group and WM-EPVS group respectively. Patients with EPVS ＜ 10 in the slice containing the maximum amount were defined as control group. Sleep quality was evaluated by the Pittsburgh Sleep Quality Index (PSQI) including seven components, where a score of 6 or higher indicated poor sleep quality. Spearman correlation analysis and binary logistic regression was performed to analyze the relationship between poor sleep quality and BG-EPVS and WM-EPVS respectively. Results: A total of 398 patients were enrolled in the study, including 114 patients in BG-EPVS group, 85 patients in WM-EPVS group. The proportion of poor sleep quality in BG-EPVS group was higher than that in control group (58.8% vs. 32.5%, P<0.001). The score of PSQI, subjective sleep quality, sleep latency, sleep duration and sleep efficiency were higher in BG-EPVS group than that in control group (P<0.05). The proportion of poor sleep quality was also higher in WM-EPVS group than that in control group (50.6% vs. 35.3%, P=0.031). The score of sleep duration and sleep disturbances were higher in WM-EPVS group than that in control group. Poor sleep quality was positively associated with BG-EPVS (rho=0.264, P<0.001) and WM-EPVS (rho=0.154, P=0.044). Binary logistic regression analysis showed that poor sleep quality, longer sleep latency and less sleep duration were independently related to BG-EPVS, and poor sleep quality, less sleep duration and more serious sleep disturbances were independently related to WM-EPVS after adjusting for confounders. Conclusion: Poor sleep quality were independently associated with EPVS in basal ganglia and white matter.